2005
DOI: 10.1044/1092-4388(2005/069)
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Fundamental Frequency Level on Voice Onset Time in Normal Adult Male Speakers

Abstract: The purpose of this study was to examine the effect of fundamental frequency (F(0)) on stop consonant voice onset time (VOT). VOT was measured from the recordings of 56 young men reading phrases containing all 6 English voiced and voiceless stops in word-initial position across high-, medium-, and low-F(0) levels. Separate analyses of variance for the voiced and voiceless stops revealed no significant main effect for F(0) for the voiced stops but a significant F(0) effect for the voiceless stops. Across the vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 52 publications
4
25
0
3
Order By: Relevance
“…It is measured from the onset of the energy 'burst' corresponding to the release of an articulatory constriction to the first of the regularly spaced vertical striations of the vocal fold vibrations [4]. VOT has been used to examine the articulatory differences across languages, genders, and motor speech impairments [5]. The control of acoustic cues to voicing requires a critically timed coordination of respiratory, phonatory and articulatory movements, so it presents a particularly challenging contrast for acquisition and for experimental analysis [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is measured from the onset of the energy 'burst' corresponding to the release of an articulatory constriction to the first of the regularly spaced vertical striations of the vocal fold vibrations [4]. VOT has been used to examine the articulatory differences across languages, genders, and motor speech impairments [5]. The control of acoustic cues to voicing requires a critically timed coordination of respiratory, phonatory and articulatory movements, so it presents a particularly challenging contrast for acquisition and for experimental analysis [1].…”
Section: Discussionmentioning
confidence: 99%
“…Factors that can effect the magnitude of VOT include physiological differences (such as age, lung volume, vocal fold tension), pathological status (hearing impairment, depression), and different linguistic tasks (speech task, speech rate, phoneme environment [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…[2] VOT is effected by some factors including physiological differences (age, gender, lung volume, vocal fold tension), pathological diseases (hearing loss, depression) and different linguistic status (speech task, speech rate, phoneme environment). [4,5] VOT values are different between languages because of their differences in structure due to originating from different language families. [4,7] There are few studies which reported about VOT in cochlear implant users.…”
Section: Discussionmentioning
confidence: 99%
“…[2] Hearing loss is a feature which can affect the significance of VOT. [4,5] Since VOT is a useful method for documenting the articulatory-phonatory aspects during the speech, we investigated and compared VOT values for Turkish stop consonants in healthy children and children with cochlear implant (CI) to clarify the effect of CI and sequential hearing rehabilitation over VOT values.…”
mentioning
confidence: 99%
“…Apesar da diversidade de possibilidades de aplicação da análise vocal digital, pode ser observada na literatura uma tendência de se investigar parâ-metros acústicos em uma população predominantemente adulta [5][6][7][8][9][10][11][12] . A população infantil é pesquisada de forma mais restrita.…”
Section: Fundamental Frequency Of Seven Oral Vowels Of Portuguese In unclassified